Awareness assessment in Turkish subpopulation with chronic oral mucosal diseases - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2015)
ABSTRACT Objectives: The aim of this study was to evaluate the awareness of group Turkish patients with chronic oral mucosal diseases by chronic oral mucosal diseases questionnaires (COMDQ). Materials and Methods: Eighty patients with chronic oral mucosal diseases were participated in the study. A detailed medical history of each patient was taken, and all the COMDQ questions, which were translated from English version, were filled out. The data were analyzed with the IBM Statistical Package for Social Sciences Statistics 22.0. Results: The mean ages of patients were 48.91 ± 13.36 years. Of the total 80 cases of chronic oral mucosal diseases identified 52 (65%) were female and 28 (35%) male. The standardized mean scores for COMDQ were 1.72 ± 1.11 for “pain and functional limitation,” 1.09 ± 0.94 for “medication and treatment,” 2.31 ± 1.06 for “social and emotional,” and 2.27 ± 0.83 for “patient support,” respectively. Conclusions: The results of this study indicate that the Turkish version of the COMDQ has the profitable psychometric peculiarity and comfortable to patients with chronic oral mucosal diseases in Turkey.